towards Artificial Intelligence-Based Adaptive E-learning systems in algerian education sector - seif eddine Touati; Lahcen Toured (My University, 2024)
During our internship, which took place in the Education Academy of the Wilaya of Souk Ahras and various educational institutions, we noted several shortcomings. To address the specific requirements of the education sector and provide innovative solutions, in this project, we designed and implemented a comprehensive framework called “Darris Bi Dhakaa,” composed of two parts: a web part and a mobile part. The web part offers an Institutional Learning Management platform called Moassassati , which is considered the foundation of the project, and a Virtual Meeting Platform named A3rad Darssek. The mobile part provides two main services: 3inek 3la Weldek and Saned Weldek. 3inek 3la Weldek is designed to keep parents informed and engaged in their child’s academic progress by providing real-time alerts and notifications. Saned Weldek is an AI-powered service aiming to assist students and their parents by offering personalized recommendations adapted to the Algerian educational context. ----------------------------------------------------------------------------- أثناء فترة التدريب التي تمت في أكاديمية التربية لولاية سوق أهراس وفي مؤسسات تعليمية مختلفة، لاحظنا عدة نقاط ضعف. للتعامل مع المتطلبات الخاصة لقطاع التعليم الجزائري وتقديم حلول مبتكرة، قمنا في هذا المشروع بتصميم وتنفيذ إطار شامل يُدعى "درس بذكاء" -. والذي يتكون من جزئين جزء ويب وجزء محمول يقدم الجزء الويب منصة لإدارة التعلم المؤسسي تُدعى "مؤسستي"، والتي تُعتبر أساس ." المشروع، بالإضافة إلى منصة للاجتماعات الافتراضية تُسمى "أعرض درسك بالإضافة إلى ذلك، يقدم الجزء المحمول خدمتين رئيسيتين: "عينك على ولدك" و"ساند ولدك". تم تصميم "عينك على ولدك" لإبقاء التعليمي الجزائري الآباء مطلعين ومشاركين في تقدم أطفالهم الدراسي من خلال تقديم تنبيهات واشعارات في الوقت الحقيقي. أما أداة "ساند ولدك" فهي خدمة تعتمد على الذكاء الاصطناعي تهدف إلى مساعدة الطلاب وأولياء أمورهم من خلال تقديم توصيات شخصية متكيفة مع السياق. ---------------------------------------------------------------------------- Lors de notre stage qui s’est déroulé au sein de l’académie d’éducation de la wilaya de Souk Ahras et dans divers établissements d’enseignement, nous avons constaté plusieurs lacunes. Pour répondre aux exigences spécifiques du secteur algérien de l’éducation et apporter des solutions innovantes, dans ce projet, nous avons conçu et mis en œuvre un cadre complet appelé « Darris Bi Dhakaa » composé de deux parties. une partie web et une partie mobile. La partie web offre une plateforme de gestion de l’apprentissage institutionnel appelée Moassassati (), qui est considérée comme la base de notre projet, et une plateforme de réunion virtuelle dont le nom est A3rad Darssek. Par ailleurs, la partie mobile propose deux services principaux : 3inek 3la Weldek et Saned Weldek. 3inek 3la Weldek est conçu pour tenir les parents informés et impliqués dans le progrès scolaire de leur enfant en fournissant des alertes et des notifications en temps réel. L’outil Saned Weldek est un service intelligent basé sur l’IA visant à assister les étudiants et leurs parents en fournissant des recommandations personnalisées adaptées au contexte éducatif algérien.